TD-DFT Study of Absorption and Emission Spectra of 2-(2′-Aminophenyl)benzothiazole Derivatives in Water - Natthaporn Manojai (2018)
© 2017, Springer Science+Business Media New York. Reduction of aromatic azides to amines is an important property of hydrogen sulphide (H 2 S) which is useful in fluorescence microscopy and H 2 S probing in cells. The aim of this work is to study the substituent effect on the absorption and emission spectra of 2-(2′-aminophenyl)benzothiazole (APBT) in order to design APBT derivatives for the use of H 2 S detection. Absorption and emission spectra of APBT derivatives in aqueous environment were calculated using density functional theory (DFT) and time-dependent DFT (TD-DFT) at B3LYP/6-311+G(d,p) level. The computed results favoured the substitution of strong electron-donating group on the phenyl ring opposite to the amino group for their large Stokes’ shifts and emission wavelengths of over 600 nm. Also, three designed compounds were suggested as potential candidates for the fluorescent probes. Such generalised guideline learnt from this work can also be useful in further designs of other fluorescent probes of H 2 S in water.